Multilobular tumor of bone in a dog - de Biasi Bassani Gonçalves, Aline; Bertolo, Paulo Henrique Leal [UNESP]; da Conceição, Maria Eduarda Bastos Andrade Moutinho [UNESP]; Magalhães, Geórgia Modé; de Barros Bandarra, Marcio; Moreira, Pamela Rodrigues Reina [UNESP]; de Oliveira Vasconcelos, Rosemeri [UNESP] (Universidade Federal do Rio Grande do Sul, 2019)
Background: Multilobular tumor of bone (MTB) is a primary bone neoplasm, uncommon in dogs. This tumor was called of many names for a long time, as: chondroma rodens, multilobular osteochondrosarcoma, multilobular osteoma, multilobular chondroma, calcificating aponeurotic fibroma, although MTB was preferred chosen, because these other name could be correlated with humans' tumors. This tumor is observed specially in skull bone, although it was reported in zygomatic arc, hard palate, axilla, spine and penis. Mostly happen in big breeds dogs, and middle to old age patients. Clinical signs depending of region and how aggressive the tumor is, usually are related to compression of any structure. The growth of MTB is frequently slow and progressive, locally invasive, occurring relapse after surgical revomal, although the tumor has low to moderate metastatic potential. The aim of this study is to report a case of MTB in a female dog and describe anatomopathological changes. Case: A female dog, mixed breed, 13 year-old, of middleweight was admitted in Pathology Department of College of Agricultural Sciences and Veterinary Medicine (FCAV-Unesp), Campus of Jaboticabal - SP, to be undergone to necropsy. The patient have never shown any epileptic crisis or neurologic signs. In macroscopic examination was found a mass in skull, which invaded the orbit and frontal sinus, but it was not invading brain cavity. The neoplasm had and irregular surface, firm consistent, color was white mixed to red areas, after cut it was granular and rough, and had some point mineralized areas. The lobs of lung had much firm masses, colored gray to white. In cytology it was observed fusiform to polyhedric isolated mesenchymal cells, moderated pleomorphic, basophilic cytoplasm, thin granulated nuclear chromatin, and visible nucleoli that was involved by eosinophilic extracellular matrix. The proposed diagnostic was bone sarcoma. Histopathological assessment showed mesenchymal neoplastic proliferation, and multilobular characteristic, the lobules had different sizes and was well organized, and they were separated by thin conjunctive septs. In the center of lobules, there was an “island” with mineralized or chondroitin bone matrix, in some of these islands there were osteoclast. The cells had moderated pleomorphism and low mitotic activity (three mitotic cells in ten high-power field). At least, it showed big necrosis areas and invasion of near tissue. In lung was observed metastatic areas, which had same histopathologic way of primary neoplasm in skull. That way, the histopathologic exam was similar to Multilobular tumor of bone grade II. Discussion: The MTB is an uncommon neoplasm, which assaults mostly skull bone in large breeds dogs and middle age of eight years old. This case accord to literature about breed size, age and local of tumor. The clinical signs in this dog was related to region what it was growing and near structure compression. Besides that, the patient had lung metastasis, that is the principal metastatic sites according to literature. The Histopathologic exam showed the same characters of MTB, which was considered grade II according to literature. Despite MTB is an uncommon neoplasm in clinic of dogs and cats, the epidemiological knowns as age, breed and localization, anatomopathological changes, and histopathological exam allows to have a diagnosis, showing the importance of including this neoplasm in differential diagnosis of bone tumor in dogs.
Tumor ósseo multilobular em um cão
Keywords: Bone tumor; Canine; Skull; Veterinary oncology